Islam, Negara, dan Hak Konstitusional: Analisis terhadap Kebebasan Beragama dalam Perspektif Hukum Islam dan UUD 1945 - Moh Alvin Kamal; Yusriansyah Yusriansyah; Muh Fadly Multazam; Kurniati Kurniati (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Freedom of religion is a fundamental right guaranteed in Islamic teachings as well as within the Indonesian constitutional framework. However, the practical implementation of this freedom has not fully aligned with the constitutional provisions that regulate it. Various events, including the restriction of worship facilities, discriminatory policies toward religious minorities, and the enforcement of blasphemy regulations, indicate a significant gap between constitutional norms and societal practices. This issue is relevant considering that religion in Indonesia is not only a sociological9 identity but also plays a normative role in the state system. This research aims to examine religious freedom from Islamic legal perspectives and analyze constitutional protection within the 1945 Constitution, while identifying points of harmonization between the two frameworks. A normative legal methodology using comparative analysis between Islamic jurisprudence and constitutional law was applied. Findings reveal that both Islam and the Indonesian Constitution recognize religious freedom while placing limits for public order, equality, and communal well-being. The Qur’anic principle la ikraha fid-din aligns with Article 28E and Article 29 of the 1945 Constitution, although implementation varies based on political and social context. This research recommends strengthening moderate Islamic interpretation and constitutional practice to ensure equal protection for all religious groups.